So close to freedom : a World War II story of peril and betrayal in the Pyrenees - Cartron, Jean-Luc E. (University of Nebraska Press, 2019)
"Drawing on government and private World War II archives, Cartron gives the first detailed account of the only failed mission of the smuggler Charbonnier--when 29 Allied soldiers in a group of 35 were captured on their way to freedom over the French Pyrenees."--Provided by publisher